ANALISIS TERHADAP PEMBERIAN OPINI LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN PEGUNUNGAN BINTANG - Irwanto Rante; Agustinus Salle; Elsyan Rienette Marlissa (Universitas Cenderawasih, 2018)
The purpose of this study is to assess the influence of Internal Control System (SPI) and non-compliance to the opinion of Financial Audit Board (BPK) on Financial Report of Local Governments. We use BPK Audit Reports from 2011 to 2014 from District of Pegunungan Bintang. We analyse the data using descriptive and quantitative analysis. The results show that the type of cases was dominated by the findings of non-compliance with the regulation, as many as 614 cases, then followed by the weakness of SPI that is 184 cases. Non-compliance causes many results for frauds.